(untitled) - Mauldin, John (Hoboken, N.J., 2006)
In Just One Thing, author John Mauldin offers an incomparable shortcut to prosperity: the personal guidance of an outstanding group of recognized financial experts, each offering the single most useful piece of advice garnered from years of investing. Conversational rather than technical in tone, each contributor's personal principle for success is illustrated with entertaining and illuminating real-life stories.
Keywords: Investments,Đầu tư